Lithium-Acetate-Mediated Biginelli One-Pot Multicomponent Synthesis under Solvent-Free Conditions and Cytotoxic Activity against the Human Lung Cancer Cell Line A549 and Breast Cancer Cell Line MCF7 - Harshita Sachdeva; Diksha Dwivedi (The Scientific World Journal)
Various Biginelli compounds (dihydropyrimidinones) have been synthesized efficiently and in high yields under mild, solvent-free, and eco-friendly conditions in a one-pot reaction of 1,3-dicarbonyl compounds, aldehydes, and urea/thiourea/acetyl thiourea using lithium-acetate as a novel catalyst without the addition of any proton source. Comparative catalytic efficiency of lithium-acetate and polyphosphoric acid to catalyze Biginelli condensation is also studied under neat conditions. The reaction is carried out in the absence of any solvent and represents an improvement of the classical Biginelli protocol and an advantage in comparison with FeCl3·6H2O, NiCl2·6H2O and CoCl2·6H2O that were used with HCl as a cocatalyst. Compared to classical Biginelli reaction conditions, the present method has advantages of good yields, short reaction times, and experimental simplicity. The obtained products have been identified by spectral (1H NMR and IR) data and their melting points. The prepared compounds are evaluated for anticancer activity against two human cancer cell lines (lung cancer cell line A549 and breast cancer cell line MCF7).